Patterns of co – occurrence of parasites in Eastern Baltic cod stocks across different depth strata - Elisa Janssen 1988- (2024)
Ritgerðin er lokuð til 29.09.2025 The cod (Gadus morhua) stock in the eastern Baltic Sea is in a poor state and lacks signs of recovery, despite historically low fishing pressure in recent years. Poor body condition is a major feature of these cod, but the reasons for this are still unclear. The present study investigates whether infection pressure from parasites could be a cause of poor body condition. Three types of parasites were analyzed: the nematode Contracaecum osculatum which infects the cod liver, the microsporidian parasite Loma morhua, which infects the gills and other organs, and acanthocephalans, which infect the cod intestines. Earlier analyses suggested that the water depth at which cod forages might influence parasite infestation rates. Our hypothesis is thus that the prevalence, as well as the intensity of infection, differs with depth stratum. In this present study, we analyzed cod (caught in August 2023) from both the Bornholm Basin and the Gdansk Deep for differences between infection rates in different depth strata. The samples were caught with bottom trawls. Biological parameters were taken from each cod, numbers of nematodes on the liver, of L. morhua on the gills, and acanthocephala in the intestines were counted and stomach contents were analyzed. All the cod examined in the present study were infected with at least one of the three parasites. The prevalence and mean intensity of infection of L. morhua as well as with acantocephala in cod examined were generally higher than C. osculatum. Cod were mainly feeding on crustaceans and less on fish. Adverse changes in environmental conditions like trophic lengthening and habitat loss due to anoxia and hypoxia may have led to a lack of food supply, impairing the food web structure. High parasite loads seem to be a sign of poor health of the Baltic cod stock rather than the key reason for the poor body condition of the fish. Generally, we observed higher prevalences and intensities of infection in Baltic cod than in cod from the North Sea or ...